Profit Shifting of Multinational Corporations Worldwide - Javier Garcia-Bernardo; Petr Jansky (Charles University in Prague, Institute of Economic Studies (IES), 2021)
We exploit the new multinational corporations' country-by-country reporting datawith unparalleled country coverage to study profit shifting to tax havens. We showthat a logarithmic function is preferable to linear and quadratic ones for modelling the extremely non-linear relationship between profits and tax rates. Using thismethodology, we reveal that multinational corporations shifted US1 trillion of profits in 2016 and that those headquartered in the United States and China did so most aggressively. We establish that the Cayman Islands is the largest tax haven, whereas countries with lower incomes tend to lose more tax revenue relative to total tax revenues.
Keywords: F23; H25; H26; H32; 330; multinational corporation; corporate taxation; profit shifting; effective tax rate; country-by-country reporting; global development